2014
DOI: 10.1111/cdev.12250
|View full text |Cite
|
Sign up to set email alerts
|

What Ever Happened to the “Cool” Kids? Long‐Term Sequelae of Early Adolescent Pseudomature Behavior

Abstract: Pseudomature behavior—ranging from minor delinquency to precocious romantic involvement—is widely viewed as a nearly normative feature of adolescence. When such behavior occurs early in adolescence, however, it was hypothesized to reflect a misguided overemphasis upon impressing peers and was considered likely to predict long-term adjustment problems. In a multi-method, multi-reporter study following a community sample of 184 adolescents from age 13 to 23, early adolescent pseudomature behavior was linked cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 57 publications
5
47
0
3
Order By: Relevance
“…Additionally, the association between precocious sexual behaviors and peer acceptance may vary in the short-term versus the long-term. For example, Allen, Schad, Oudekerk, and Chango (2014) recently found that making out was associated with increased peer status during early adolescence, but that the correlation weakened over age. Moreover, they also found that precocious sexual and minor delinquent behaviors were associated with long-term romantic relationship difficulties and increased substance use and criminal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the association between precocious sexual behaviors and peer acceptance may vary in the short-term versus the long-term. For example, Allen, Schad, Oudekerk, and Chango (2014) recently found that making out was associated with increased peer status during early adolescence, but that the correlation weakened over age. Moreover, they also found that precocious sexual and minor delinquent behaviors were associated with long-term romantic relationship difficulties and increased substance use and criminal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the cited studies (Luthar & McMahon, 1996; Rodkin et al, 2006) used cross-sectional data, so they could not identify groups that followed different behavioral trajectories or test how the peer acceptance of individuals in these groups changed over time. Other studies (Allen et al, 2014; Cillessen & Mayeux, 2004) used longitudinal data, but focused on changes in the association of between-person differences in antisocial behavior with between-person differences in peer acceptance (e.g., whether the cross-sectional association between antisocial behavior and peer acceptance differed over time). Still others used longitudinal data but did identify individuals who were persistently antisocial (e.g., Dijkstra et al, 2010; Juvonen et al, 2012) to test whether they followed different trajectories of peer acceptance than their peers.…”
Section: Peer Acceptance Of Persistently Antisocial Adolescentsmentioning
confidence: 99%
“…As compared to children, adolescents spend significantly more time with peers, experience more frequent peer-based stressors, and exhibit heightened emotional reactivity to peer stress (Brown and Larson 2009; Rudolph 2014). Prior research suggests that adolescents’ peer experiences are prospectively associated with educational outcomes, mental health symptoms, addictive behaviors, and even physical health morbidity and mortality decades later (Allen et al 2014; Almquist 2009; Almquist and Östberg 2013; Menting et al 2016; Modin et al 2011; Moffitt 1993). However, youth are now increasingly turning to social media as a primary means of interaction with peers, requiring investigators to reconsider prior conceptualizations of the peer context (Lenhart 2015a; Rideout 2015).…”
Section: Introductionmentioning
confidence: 99%